Surgical management of cervico-mediastinal goiters: Our experience and review of the literature. (April 2016) - Di Crescenzo, V.; Vitale, M.; Valvano, L.; Napolitano, F.; Vatrella, A.; Zeppa, P.; De Rosa, G.; Amato, B.; Laperuta, P.
Abstract: Aim: We analyze and discuss the clinical presentation, the diagnostic procedures and the surgical technique in relation to post-operative complications and results in cervico-mediastinal thyroid masses admitted in Thoracic Surgery Unit of AOU Second University of Naples from 1991 to 2006 and in Thoracic Surgery Unit of AOU "S. Giovanni di Dio & Ruggi D'Aragona" of Salerno over a period of 3 years (2011–2014). Methods: We reviewed 97 patients who underwent surgical treatment for cervico-mediastinal goiters. 47 patients (49.2%) had cervico-mediastinal goiter, 40 patients (40%) had mediastino-cervical goiter and 10 patients (10.8%) had mediastinal goiter. 73 cases were prevascular goiters and 24 were retrovascular goiters. We performed total thyroidectomy in 40 patients, subtotal thyroidectomy in 46 patients and in 11 cases the resection of residual goiter. In 75 patients we used only a cervical approach, in 21 patients the cervical incision was combined with median sternotomy and in 1 patient with transverse sternotomy. Results: Three patients (3.1%) died in the postoperative period (2 cardio-respiratory failure and 1 pulmonary embolism). The histologic study revelead 8 (7.7%) carcinomas. Postoperative complications were: dyspnea in 9 cases (10.7%), transient vocal cord paralysis in 6 patients (9.2%), temporary hypoparathyroidism in 9 patients (9.2%) and kidney failure in 1 case (0.9%). Conclusions: The presence of a cervico-mediastinal thyroid mass with or without respiratory distress requires a surgical excision as the only treatment option. Thyroid masses extending to the mediastinum can be excised successfully by cervical incision. Bipolar approach (cervical incision and sternotomy) has an excellent outcome, achieving a safe resection, especially in large thyroid masses extending to the mediastinum with close relations to mediastinal structures and in some limited cases (carcinoma, thyroiditis, retrovascular goiter, ectopic goiter). Postoperative mortality and morbidity is very low, independent of surgical techniques. Other surgical approaches for excision of a Posterior Mediastinal Thyroid Goiter reported in literature are: VATS techniques to remove an ectopic intrathoracic goiter, robot-assisted technique for the removal of a substernal thyroid goiter, with extension into the posterior mediastinum.